Contradictions of indigenous cognition and heritage evaluation under political transformations in a working-class community in Tianjin, China. (January 2023) - Zhang, Jingmei; Xu, Subin; Aoki, Nobuo
Abstract: Over the past few decades, China has undergone thorough reforms. Changes triggered by deindustrialization, market orientation, and land utilization have led to the demolition, replacement, and regeneration of traditional industrial neighborhoods in urban centers. Meanwhile, the indigenous residents, who used to be members of the working class in the Danwei era, have lost the protection of state-owned enterprises, or "Danwei", and suffered from social disparity, displacement, identity loss, and trauma amid the socialist deindustrialization process. As a socialist country dedicated to regulating overcapitalization and social polarization, neoliberal China has been committed to exploring moderate social transformation strategies in the process of deindustrialization in recent years. In the given example of Tianjin's Mian 3 (an urban regeneration project of an old textile industrial community), both qualitative and quantitative analyses are employed to evaluate the cognitive complexities of residents' needs and place attachment in relation to heritage evaluation. The results from these analyses are further used to examine the problems in the redevelopment of industrial heritage communities and the social expression of the working class. The research shows that the cognitive complexity of the working class should be included in the social value of industrial heritage protection and given more importance in the process of coordinating the development of industrial heritage and its surroundings. In the context of ongoing deindustrialization and urban redevelopment of industrial heritage communities in China and the rest of the world, this study provides theoretical support and data for understanding working-class residents and building sustainable and caring heritage communities.